Evidence from oyster suggests an ancient role for Pdx in regulating insulin gene expression in animals - Fei Xu (Nature Portfolio, 2021)
In vertebrates insulin is a direct transcriptional target of Pdx: the same is true in Pacific oysters and the authors show insulin-related gene, cgILP, is co-expressed with cgPdx in oyster digestive tissue, showing this gene interaction dates back to the origin of Bilateria.